Intergenerational ties and case fatality rates: A cross-country analysis - Christian Bayer; Moritz Kuhn (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
COVID-19 is spreading and has reached the state of a worldwide pandemic and health systems are or will be tested in how they can deal with it. So far, during this early phase of the pandemic, outcomes in terms of case-fatality rates (CFR) differ widely across countries. We explore how differences in living arrangements of generations within families contribute to the cross country differences. We document a strong positive correlation between countries' CFRs and the share of working-age families living with their parents. This suggest that policy needs to focus on inter-generational social distance when combating this pandemic.
Keywords: 330